The Money Formula Dodgy Finance, Pseudo Science, and How Mathematicians Took Over the Markets - Wilmott, Paul; Orrell, David (Ascent Audio, 2024)
Explore the deadly elegance of finance's hidden powerhouse The Money Formula takes you inside the engine room of the global economy to explore the little-understood world of quantitative finance, and show how the future of our economy rests on the backs of this all-but-impenetrable industry. Written not from a post-crisis perspective--but from a preventative point of view--this book traces the development of financial derivatives from bonds to credit default swaps, and shows how mathematical formulas went beyond pricing to expand their use to the point where they dwarfed the real economy. You'll learn how the deadly allure of their ice-cold beauty has misled generations of economists and investors, and how continued reliance on these formulas can either assist future economic development, or send the global economy into the financial equivalent of a cardiac arrest. Rather than rehash tales of post-crisis fallout, this book focuses on preventing the next one. By exploring the heart of the shadow economy, you'll be better prepared to ride the rough waves of finance into the turbulent future.
Audio book. - Online resource; title from title details screen (cloudLibrary, viewed November 28, 2024)
Keywords: Risk management; Finance -- Mathematical models; Options (Finance) -- Mathematical models; Gestion du risque; Finances; Modèles mathématiques; Options (Finances); Modèles mathématiques; risk management; Corporate Finance; BUSINESS & ECONOMICS; Audiobooks; Livres audio